2021
DOI: 10.48550/arxiv.2102.06523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of exoplanet phase curves with Ariel

Benjamin Charnay,
Joao M. Mendonça,
Laura Kreidberg
et al.

Abstract: The ESA-Ariel mission will include a tier dedicated to exoplanet phase curves corresponding to ∼10% of the science time. We present here the current observing strategy for studying exoplanet phase curves with Ariel. We define science questions, requirements and a list of potential targets. We also estimate the precision of phase curve reconstruction and atmospheric retrieval using simulated phase curves. Based on this work, we found that full-orbit phase variations for 35-40 exoplanets could be observed during… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…to exoplanet phase curves, observing a planet throughout its entire orbit (e.g. Stevenson et al 2017;Changeat et al 2021a;Dang et al 2021;May et al 2021), and studies are underway to find the best targets for phase curve studies with Ariel (Charnay et al 2021;Moses et al 2021). Additionally, this time could be utilised to observe small, rocky worlds which may host secondary atmospheres, as outlined in E19.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…to exoplanet phase curves, observing a planet throughout its entire orbit (e.g. Stevenson et al 2017;Changeat et al 2021a;Dang et al 2021;May et al 2021), and studies are underway to find the best targets for phase curve studies with Ariel (Charnay et al 2021;Moses et al 2021). Additionally, this time could be utilised to observe small, rocky worlds which may host secondary atmospheres, as outlined in E19.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…While not discussed here, Ariel has a fourth tier to account for targets or observations that do not fit into the main structure of the survey. Much of this time might be dedicated to exoplanet phase curves, observing a planet throughout its entire orbit (e.g., Stevenson et al 2017;Changeat et al 2021a;Dang et al 2022;May et al 2021), and studies are underway to find the best targets for phase curve studies with Ariel (Charnay et al 2021;Moses et al 2021). Additionally, this time could be utilized to observe small, rocky worlds that may host secondary atmospheres, as outlined in E19.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…In this work we have shown that hierarchical models are useful when analyzing repeated measurements from a single target, or when doing comparative exoplanetology studies of many targets. Next generation telescopes like James Webb and Ariel will make repeated measurements of certain targets, and will both carry out photometric and spectroscopic transit, eclipse, and phase curve surveys for a variety of targets (Bean et al 2018;Tinetti et al 2018;Charnay et al 2021). This will allow for atmospheric characterization of potentially thousands of more exoplanets, from Earth-like planets to ultra-hot Jupiters, and we recommend that these comparative surveys incorporate hierarchical modelling to make measurements and predictions that are as robust as possible.…”
Section: Discussionmentioning
confidence: 99%